Precipitation Patterns in Reaction–Diffusion–Reaction Systems of Prussian Blue and Cu–Fe-Based Prussian Blue Analogs - Hayashi, Hisashi (Frontiers in Physics, 2022)
In agarose gel containing [Fe(CN)6]3‒ ions and sandwiched between two metal rods (Ti, Fe, or Cu) with a voltage of 1‒5 V applied for 20‒100 h, reaction–diffusion–reaction (RDR) processes (that is, electrochemical reactions at metal rods to generate reactant ions, diffusion of the reactant ions influenced by the electric field in agarose gel, and reactions of the reactant ions to form/decompose precipitates) were coupled to generate diverse precipitation patterns of Prussian blues (PB) or Cu–Fe-based Prussian blue analogs (Cu–Fe PBA). These patterns strongly depended on the type of metal electrode, applied voltage, initial [Fe(CN)6]3‒ concentration, and elapsed time after voltage application. Under the application of 2 V for 20/50 h, the PB/Cu–Fe PBA formed a discrete precipitation band on the anode/cathode side in an agarose gel containing 0.050 M [Fe(CN)6]3‒ ions. In the Cu–Fe PBA system, a relatively long precipitation band of Cu(OH)2 was also generated on the anode side by OH‒ ions produced on the cathode as a byproduct. Longer voltage applications promoted propagation of the Cu–Fe PBA band to the anode side and caused the discrete PB band to disappear. Higher initial [Fe(CN)6]3‒ concentrations deepened the color of the generated patterns. Higher voltage applications suppressed the propagation of the Cu–Fe PBA band to the anode side and caused the PB band to disappear. Experiments using a Ti cathode suggested that the formation and subsequent decomposition of PB or Cu–Fe PBA at the cathode surface are important for forming precipitation band(s) in the gel near the cathode. The application of cyclic alternating voltages (particularly, 4 V for 1 h and 1 V for 4 h) was effective in generating Liesegang-band-like periodic bands, particularly for the Cu–Fe PBA system.